Molecular and Biochemical Characterization of a Salt Tolerant α-Amylase Producing Isolate NH-25 - Mahnaz Ahmad; Raheela Rahmat Zohra; Shah Ali Ul Qader (Journal of Basic & Applied Sciences, 2018)
Halophiles are considered as important sources of extremozymes that are not only salt tolerant but can catalyze reactions efficiently under harsh conditions of various industrial processes. Among industrially important enzymes alpha amylase is used in many industries such as starch, pharmaceutical, detergent, paper, food, and textile. Due to wide applications there is a continuous need for novel sources of the enzyme to be discovered. One of the new variant from various amylase producing isolates of marine samples of Arabian Sea, an industrial dumping site and a rich natural source, particularly for microbes, a salt tolerant α-amylase producer was studied. This isolate based on cultural characteristics, biochemical tests and molecular characterization inferred from 16s rDNA sequencing identified as Bacillus subtilis NH-25.